ChemInform Abstract: Structural and Optical Studies of KErP2O7 Diphosphate. Issue 47 (3rd November 2016) - Chaker, M.; Horchani‐Naifer, K.; Ferid, M.
Abstract: KErP2 O7 is prepared by solid state reaction of a stoichiometric mixture of K2 CO3, (NH4 )2 HPO4, and Er2 O3 (Pt crucible, 650 °C, 48 h).